2022
DOI: 10.1186/s40168-022-01315-x
|View full text |Cite
|
Sign up to set email alerts
|

Colistin-degrading proteases confer collective resistance to microbial communities during polymicrobial infections

Abstract: Background The increasing prevalence of resistance against the last-resort antibiotic colistin is a significant threat to global public health. Here, we discovered a novel colistin resistance mechanism via enzymatic inactivation of the drug and proposed its clinical importance in microbial communities during polymicrobial infections. Results A bacterial strain of the Gram-negative opportunistic pathogen Stenotrophomonas maltophilia capable of degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“… Lee et al (2022) purified and identified a serine colistin-degrading protease (Cdp) in S. maltophilia strain Col1. Isolated from the soil, this strain exhibited high-level resistance against colistin (MIC value of 32 mg/L).…”
Section: Secretion Systems and Extracellular Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“… Lee et al (2022) purified and identified a serine colistin-degrading protease (Cdp) in S. maltophilia strain Col1. Isolated from the soil, this strain exhibited high-level resistance against colistin (MIC value of 32 mg/L).…”
Section: Secretion Systems and Extracellular Enzymesmentioning
confidence: 99%
“…In contrast, coinfection of flies with S. maltophilia strains carrying the cdp gene, did not increase the survival rate after colistin treatment. The authors noted that S. maltophilia genomes contain genes orthologous to cdp , located in a region immediately adjacent to the T2SS gene cluster ( Lee et al, 2022 ). Thus, the colistin-degrading protease may play an important role in collective resistance to colistin in polymicrobial infections such as CF ( Lee et al, 2022 ).…”
Section: Secretion Systems and Extracellular Enzymesmentioning
confidence: 99%
“…Additionally, S. maltophilia can play a significant role in microbiological co-infections. For instance, S. maltophilia has been found to provide significant levels of protection against antibiotics for Pseudomonas aeruginosa , which would otherwise be susceptible to them ( Bottery et al., 2022 ; Lee et al., 2022 ) and interfere with the isolation cultures and drug sensitivity tests of Mycobacterium tuberculosis , potentially leading to alterations in treatment plans and an escalation in the burden of the disease ( Li et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The last resort antibiotic colistin is also not suitable despite the demonstrated in vitro activity because half of the isolates are actually resistant to this antibiotic [ 34 ]. In addition, a recent study described a colistin-degrading protease in an environmental S. maltophilia isolate [ 35 ]. Co-cultivation experiments demonstrated that this enzyme can inactivate colistin and thereby protect an otherwise susceptible P. aeruginosa strain.…”
Section: Introductionmentioning
confidence: 99%